Stoic Influences on Plotinus’ Theodicy? - Viktor Ilievski (Elpis)
The aim of this paper is twofold: a) to identify the Stoic-attempted solutions to the problem of evil, allegedly appropriated by Plotinus and made use of in his main work on theodicy, which was divided by Porphyry into two treatises and published under the titles On Providence I. and II. (Ennead III. 2 and 3); and b) to demonstrate that the most significant theodicean strategies applied by the Stoics and later utilized by Plotinus are either of direct Platonic origin, or else might have been inspired by certain passages from Plato’s dialogues. As a side issue, it will be shown that the Stoic answers to the problem of evil that do not concur with the Platonic approach – with a single exception – are not taken into consideration by Plotinus. This is not to say that the Stoics’ contributions to the field of theodicy exerted no influence on Plotinus, but that in the counterfactual scenario where they never wrote on providence and theodicy, Plotinus would have nevertheless been able to compose a theodicy that is very similar to the present one, relying chiefly, if not exclusively, on Platonic sources and his own ideas.